Dear Tabby - Crimi, Carolyn (HarperCollinsPublishers, 2011)
A feline advice columnist assists other animals with their problems, such as a parrot whose owners complain that he talks too much, a groundhog who feels the pressure of predicting the weather, and a cat who objects to being pampered.